Hybrid Encryption Algorithms over Wireless Communication Channels - Shaheen, Mai Helmy Ahmed, 1981- (CRC Press, 2021)
This book presents novel hybrid encryption algorithms that possess many different characteristics. In particular, Hybrid Encryption Algorithms over Wireless Communication Channels, examines encrypted image and video data for the purpose of secure wireless communications. A study of two different families of encryption schemes are introduced: namely, permutation-based and diffusion-based schemes. The objective of the book is to help the reader selecting the best suited scheme for the transmission of encrypted images and videos over wireless communications channels, with the aid of encryption and decryption quality metrics. This is achieved by applying number-theory based encryption algorithms, such as chaotic theory with different modes of operations, the Advanced Encryption Standard (AES), and the RC6 in a pre-processing step in order to achieve the required permutation and diffusion. The Rubik's cube is used afterwards in order to maximize the number of permutations. Transmission of images and videos is vital in today's communications systems. Hence, an effective encryption and modulation schemes are a must. The author adopts Orthogonal Frequency Division Multiplexing (OFDM), as the multicarrier transmission choice for wideband communications. For completeness, the author addresses the sensitivity of the encrypted data to the wireless channel impairments, and the effect of channel equalization on the received images and videos quality. Complete simulation experiments with MATLAB codes are included. The book will help the reader obtain the required understanding for selecting the suitable encryption method that best fulfills the application requirements.
Introduction.Fundamentals of Image Encryption for Wireless Communication. Rubik's Cube Encryption for Wireless Communications. Hybrid Rubik's Cube Algorithm for Wireless Communications. Proposed Hybrid Encryption Frameworkfor Reliable 3-D Wireless Video Communications. Conclusions and Future Work. References.
OCLC-licensed vendor bibliographic record.
Keywords: Data encryption (Computer science); Wireless communication systems -- Security measures; COMPUTERS / Networking / General; TECHNOLOGY / Electricity